Social Harmony at the Boundaries of the Welfare State: Immigrants and Social Transfers - Gil S. Epstein; Arye L. Hillman (Institute for the Study of Labor (IZA), 2000)
The social contract of the welfare state can be strained by the arrival of immigrants who receive welfare payments financed by citizens? taxes. We show, however, that the presence of unemployed immigrants receiving welfare payments is consistent with social harmony. The social harmony, which is a consequence of a view of unemployment as a labor-market discipline, contrasts with the social conflict predicted by Karl Marx when he proposed his earlier version of the same explanation for unemployment. We demonstrate that a socially harmonious policy is always feasible. Outcomes without social harmony can therefore always be suitably amended.
Keywords: I38; F22; P16; 330; Welfare state; social harmony; immigrants; Sozialtransfer; Einwanderung; Sozialstaat; Verfassungsökonomik; Theorie